2012
DOI: 10.1073/pnas.1214102110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical analysis of the assembly and function of the yeast pre-mRNA 3′ end processing complex CF I

Abstract: The accuracy of the 3′-end processing by cleavage and polyadenylation is essential for mRNA biogenesis and transcription termination. In yeast, two poorly conserved neighboring elements upstream of cleavage sites are important for accuracy and efficiency of this process. These two RNA sequences are recognized by the RNA binding proteins Hrp1 and Rna15, but efficient processing in vivo requires a bridging protein (Rna14), which forms a stable dimer of heterodimers with Rna15 to stabilize the RNA-protein complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Subunit–subunit interactions in CF IA have been reported through pairwise assays either with the two-hybrid analysis or by pairwise association/expression ( 13 , 16 , 17 , 20 , 41 , 43 , 53 ) giving rise to a refined interaction map in CF IA ( 26 ). However, interactions between two proteins that require a third stabilizing protein may not be detected, as for example with the PYM protein interaction with Mago and Y14 ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subunit–subunit interactions in CF IA have been reported through pairwise assays either with the two-hybrid analysis or by pairwise association/expression ( 13 , 16 , 17 , 20 , 41 , 43 , 53 ) giving rise to a refined interaction map in CF IA ( 26 ). However, interactions between two proteins that require a third stabilizing protein may not be detected, as for example with the PYM protein interaction with Mago and Y14 ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular characterization of the RNA recognition motif (RRM) domain of Rna15, and the orthologue CstF-64, reveal aspects of pre-mRNA binding ( 23 ). Increased RNA sequence specificity has also been demonstrated with structural details of the auxiliary subunit Hrp1 (also known as CF IB or Nab4), and in particular within a Hrp1–Rna15–RNA ternary complex ( 24 26 ). A connection to the largest subunit of RNA polymerase II, Rpb1 is mediated by the C-terminal interacting domain (CID) of Pcf11 that binds to the Rpb1 C-terminal YSPTSPS heptamer repeats with phosphorylation on the serine in position 2 ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 96%
“…Like Hrp1, several of these proteins may contribute to DEF1 pA 1 site recognition. Rna15 and Rna14 are also members of CFI, and while Rna15 recognizes pA site positioning elements, Rna14 is capable of bridging Rna15 and Hrp1 in a CFI complex ( Gross and Moore 2001 ; Barnwal et al 2012 ). Cft2 is a component of the core CPF that binds the CYC1 pA site in vitro and crosslinks near pA sites in vivo , as well as interacting with the Pol II CTD ( Dichtl and Keller 2001 ; Kyburz et al 2003 ; Baejen et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Rna15, when complexed with Hrp1, utilizes the secondary site to recognize the A-rich PE (99) (Fig. 2F) and by itself recognizes a U-rich consensus upstream of the cleavage site (26, 27) in a scenario in which CFI contains two copies of Rna15 but only one copy of Hrp1 (88,100).…”
Section: Cstfmentioning
confidence: 99%